"Trauma-Informed" Ideas in English Education: Discussing the Scientific Evidence Base and Exploring the Discursive and Practice Effects - Niamh Storey; Sally Neaum (International Journal of School Social Work, 2021)
The UK has been slower to adopt "trauma-informed" ideas than the United States, and despite policies across the devolved governments of Northern Ireland, Wales and Scotland, there remains no clear overarching strategy in English policy. Despite this, there is observable interest in adopting "trauma-informed" practices on a more localised level across England, but the range of approaches labelled as such is varied and disparate. The scientific evidence-base for "trauma-informed" educational practices is discussed and the discursive effects of these ideas when accepted as a basis for practice are explored. Two different conceptualisations of social justice frame this discussion. We argue that whilst social justice as equity is closely aligned to the aims of trauma-informed principles in education, existing policy commitments perpetuate an idea of social justice as harmony, and this may provide a barrier to implementing these principles in practice. Local efforts to embed trauma-informed principles in English educational contexts are, therefore, challenged by existing dominant practices and ideas. The ways in which these dominant ideas enter into local "trauma-informed" approaches are explored. Three cases involving educators and wider support professionals are discussed according to their potential to promote trauma-informed principles and contribute to achieving equitable outcomes. The paper concludes the highly-localised nature of "trauma-informed" educational approaches across England, in the absence of an overarching strategy and wider policy, financial or political support, does not sufficiently contribute towards more equitable outcomes for disadvantaged students experiencing trauma or adversity.
Keywords: Adverse Childhood Experiences; ACEs; Trauma-Informed Practice; Trauma-Informed Education; Social Justice; Education Policy